Effect of electrostatic interactions on the ultrafiltration behavior of charged bacterial capsular polysaccharides. (21st October 2016) - Hadidi, Mahsa; Buckley, John J.; Zydney, Andrew L.
Abstract : Charged polysaccharides are used in the food industry, as cosmetics, and as vaccines. The viscosity, thermodynamics, and hydrodynamic properties of these charged polysaccharides are known to be strongly dependent on the solution ionic strength because of both inter‐ and intramolecular electrostatic interactions. The goal of this work was to quantitatively describe the effect of these electrostatic interactions on the ultrafiltration behavior of several charged capsular polysaccharides obtained from Streptococcus pneumoniae and used in the production of Pneumococcus vaccines. Ultrafiltration data were obtained using various Biomax™ polyethersulfone membranes with different nominal molecular weight cutoffs. Polysaccharide transmission decreased with decreasing ionic strength primarily because of the expansion of the charged polysaccharide associated with intramolecular electrostatic repulsion. Data were in good agreement with a simple theoretical model based on solute partitioning in porous membranes, with the effective size of the different polysaccharide serotypes evaluated using size exclusion chromatography at the same ionic conditions. These results provide fundamental insights and practical guidelines for exploiting the effects of electrostatic interactions during the ultrafiltration of charged polysaccharides. © 2016 American Institute of Chemical Engineers Biotechnol. Prog., 32:1531–1538, 2016